Akulturasi Pada Gereja Kristen Pniel Blimbingsari- Bali - Indrianto, Enrike Puspita (Intra, 2013)
Peniel Church is one of the examples of buildings that have been acculturated by the Balinese culture. Acculturation is a social process that arises when a group of people with a particular culture are exposed to the elements of a foreign culture so foreign element else it is gradually accepted and processed into the culture itself without causing the loss of cultural identity. Peniel Church Blimbingsari so this is one that deserves to be studied object uniqueness, whether the influences that occur after the prior acculturation acculturation, and what are the underlying philosophy-filosfi acculturation on the Blimbingsari Peniel Church. By using interpretivism, it will show the acculturation of spatial, sanctity, and cultural influences occur at Peniel Church Blimbingsari-Bali. Of the analysis will be able to prove that the Peniel Church Blimbingsari is a product design that has been acculturated between Balinese culture and Western culture.